2007
DOI: 10.1007/s10955-007-9307-z
|View full text |Cite
|
Sign up to set email alerts
|

A Borel Transform Method for Locating Singularities of Taylor and Fourier Series

Abstract: Given a Taylor series with a finite radius of convergence, its Borel transform defines an entire function. A theorem of Pólya relates the large distance behavior of the Borel transform in different directions to singularities of the original function. With the help of the new asymptotic interpolation method of van der Hoeven, we show that from the knowledge of a large number of Taylor coefficients we can identify precisely the location of such singularities, as well as their type when they are isolated. There … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 41 publications
0
37
0
Order By: Relevance
“…Such a scheme can in principle be carrried over to the case with a boundary; this will, of course, require the numerical solution of the elliptic (Poisson) equations with both Dirichlet and Neumann boundary conditions involved in the Helmholtz-Hodge decompositions. For the case of a boundary that is not analytic, but in a suitable ultradifferential class, the time-Taylor series will generally be divergent for any t > 0, so that some resummation method (e.g., by a Borel transformation [55]) must also be used for the numerical implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Such a scheme can in principle be carrried over to the case with a boundary; this will, of course, require the numerical solution of the elliptic (Poisson) equations with both Dirichlet and Neumann boundary conditions involved in the Helmholtz-Hodge decompositions. For the case of a boundary that is not analytic, but in a suitable ultradifferential class, the time-Taylor series will generally be divergent for any t > 0, so that some resummation method (e.g., by a Borel transformation [55]) must also be used for the numerical implementation.…”
Section: Discussionmentioning
confidence: 99%
“…We found that, when using 50-80 quadruple-precision Taylor coefficients from our L 2 series, such methods allow a determination of the radius of convergence with an error in the range 10%-20%. We also tried more advanced extrapolation techniques, such as convergence acceleration methods (see, e.g., [35,34] and references therein) and the asymptotic extrapolation technique [25,35,34], which have the potential of capturing both leading and subleading asymptotic behaviour. Unfortunately, all these techniques failed to reach the asymptotic regimes and thus gave no improvement over the more standard ones.…”
Section: Appendix B Computation Of the Radius Of Convergence Of A Pomentioning
confidence: 99%
“…We shall also address a new question: scaling exponents are notoriously known with poor accuracy (cf., e.g., [4]); how accurately can we determine such exponents by working with Reynolds number at which there are significant subdominant corrections to scaling? Using recent results of van der Hoeven [8,9], we shall show that this requires a subtle tradeoff between Reynolds numbers and precision (number of decimal digits) used in the calculations.We begin with simulation-based results for the Reynolds number dependence of gradmoments when standard double-precision calculations suffice. We follow here the same strategy as in Ref.[6]: we solve the Burgers equation (2) with the initial condition u 0 (x) = sin x, using a pseudo-spectral method combined with fixedtime-step fourth-order Runge-Kutta time marching and a slaved scheme, known by the acronym ETDRK4 [10], for handling the viscous dissipation.…”
mentioning
confidence: 91%
“…We shall also address a new question: scaling exponents are notoriously known with poor accuracy (cf., e.g., [4]); how accurately can we determine such exponents by working with Reynolds number at which there are significant subdominant corrections to scaling? Using recent results of van der Hoeven [8,9], we shall show that this requires a subtle tradeoff between Reynolds numbers and precision (number of decimal digits) used in the calculations.…”
mentioning
confidence: 91%
See 1 more Smart Citation